THE EFFECTIVENESS OF USING DUOLINGO IN TEACHING VOCABULARY TO CAMP CLASS AT LANGUAGE CENTER - Muhammad Miftahul Hia; Muhyidin, M. Syaichul; Setyawan, Wawan Herry (University of Muhammadiyah Malang, 2024)
This study seeks to determine the effectiveness of the Duolingo app as a gamification-based learning tool for teaching vocabulary in order to assist students in improving their English language skills. This study used a quasi-experimental design with a Nonequivalent Control Group Design, which splits the class into two groups: experimental and control. The data was collected by developing vocabulary questions for both pre- and post-tests. The statistical tool from SPSS version 22 was used to analyse the data. The study's findings demonstrate how effective the Duolingo program is in helping students improve their English vocabulary. The independent sample t-test resulted in a Sig. (2-tailed) value of 0.000, which is statistically significant and less than 0.05. Furthermore, the average pre-test score (69.44 before using the Duolingo app) and post-test score (85.83 after using the Duolingo app) increased. This shows that students who were taught using the Duolingo app had different vocabulary mastery outcomes than those who were taught using traditional techniques or without the app. The Duolingo software is significantly more effective in helping students improve their vocabulary. Following the adoption of the Duolingo program, the Language Center noticed an improvement in its pupils' vocabulary.